Comparative study of sonohysterosalpingography with hysterosalpingography for determination of tubal patency in infertile women - Kumari, Renuka; Sahay, Priti Bala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Ever since the history of mankind, human infertility has been a source of personal misery and social stigma. The aim of this study was to evaluate the tubal factors of infertility, especially the tubal patency by SSG and HSG and study the advantages of both. Methods: The present work was undertaken in the Department of Obstetrics and Gynecology and Department of Radiodiagnosis of Rajendra Institute of Medical Sciences, Ranchi. 60 patients with primary or secondary infertility attending the OPD were selected over a period of 15 months (July 2008 to September 2009). Inclusion criteria: women of age 20-35 years with regular menstrual cycle whose male partners had no faults. Exclusion criteria: women with PID or other proven causes of infertility. All the patients were subjected to both SSG and HSG (interval period being 1 menstrual cycle) and the results compared in terms of tubal occlusion detection rate, detection of pelvic pathologies and complications of both the procedures. Results: Out of 60 cases, 70% (42) were of primary infertility and 30% (18) were of secondary infertility. History of reproductive tract infections was higher in secondary infertility group (44%). SSG appeared to be more sensitive in detection of tubal obstruction (35%) than HSG (30%), but the difference was statistically insignificant (p>0.05). HSG could locate the exact site of tubal obstruction which was not evident in SSG. SSG was more sensitive in detection of associated pelvic pathologies (p = 0.05) like ovarian cyst, endometriosis and fibroid uterus. However, HSG was better in diagnosis of genital tuberculosis. 20% of patients complained of pelvic pain, bleeding, infection or allergic reaction during or after HSG, while only 7% of patients reported the same with SSG. Thus, SSG was superior to HSG in this respect (p = 0.02). Conclusions: SSG, though not a substitute, can be used as an alternative to HSG for assessment of tubal factors of infertility.